Severe COVID-19 Infection and Pediatric Comorbidities: A Systematic Review and Meta-Analysis. (February 2021) - Tsankov, Boyan K.; Allaire, Joannie M.; Irvine, Michael A.; Lopez, Alison A.; Sauvé, Laura J.; Vallance, Bruce A.; Jacobson, Kevan
Highlights: What is known Adults with comorbidities are more likely to suffer from severe manifestations of COVID-19 Children with COVID-19 have less severe disease manifestations than adults Children may experience multisystem inflammatory syndrome due to COVID-19 What is new Children with comorbidities may be at an increased risk for PICU admission and/or severe COVID-19 Children with comorbidities may be at an increased risk of mortality during COVID-19 infection Childhood obesity likely contributes to more serious manifestations of COVID-19 Abstract: Objective: There is limited information on the severity of COVID-19 infection in children with comorbidities. We investigated the effects of pediatric comorbidities on COVID-19 severity by means of a systematic review and meta-analysis of published literature. Methods: PubMed, Embase, and Medline databases were searched for publications on pediatric COVID-19 infections published January 1 st to October 5 th, 2020. Articles describing at least one child with and without comorbidities, COVID-19 infection, and reported outcomes were included. Results: 42 studies containing 275, 661 children without comorbidities and 9, 353 children with comorbidities were included. Severe COVID-19 was present in 5.1% of children with comorbidities, and in 0.2% without comorbidities. Random-effects analysis revealed a higher risk of severe COVID-19 among children with comorbidities than for healthy children; relative risk ratio 1.79 (95% CI 1.27 – 2.51; I 2 = 94%). Children with underlying conditions also had a higher risk of COVID-19-associated mortality; relative risk ratio 2.81 (95% CI 1.31 – 6.02; I 2 = 82%). Children with obesity had a relative risk ratio of 2.87 (95% CI 1.16 – 7.07; I 2 = 36%). Conclusions: Children with comorbidities have a higher risk of severe COVID-19 and associated mortality than children without underlying disease. Additional studies are required to further evaluate this relationship.